Adequate Financing And Agricultural Production: Response To New Generation Agriculture In Cameroon - Mbu Daniel Tambi; Wirbam Juliet Bime (JASc (Journal of Agribusiness Sciences), 2019)
Food insecurity, malnutrition and hunger are persistent within the urban and rural areas in Cameroon resulting from inadequate development policy approaches. As a step to solve this problem, our study seeks principally to: evaluate the impact of adequate financing on agricultural production. Use is made of control function modeling. Empirical results are based on 2007 household consumption survey and statistics from Ministry of Agriculture. The result shows that adequate financing is strongly correlated with agricultural production, while results by type and nature of agricultural credit show that personal financing, bank and micro-financial institution, family and partners, friends and tontines and institutional support is increasing agricultural production. Further, subsidies in kind contribute more in augmenting agricultural production as compared to subsidies in cash. These results have implications for addressing the food security problem and poverty reduction in terms of improving agricultural productivity through adequate financing and subsidies in kind and income growth in this period of economic emergence.